THE EVALUATION OF ENGLISH SPEAKING SKILL OF SERVERS AT LAKEVIEW RESTAURANT KINTAMANI, BALI IN SERVING FOOD AND BEVERAGE ORDERS - Francisca Titing Koerniawaty; I Nyoman Sudiarta; Made Krisna Adi Chandra; I Putu David Adi Saputra (Institut Pariwisata dan Bisnis Internasional, 2015)
The aim of this study was to evaluate the English speaking skill of servers at Lakeview Restaurant-Kintamani, Bali in serving food and beverage orders, and focused on serving â€œAâ€™la carte menuâ€ orders. The problems of speaking in English often faced by servers are less confident talking to guests when handling them during breakfast, lunch or dinner. This case may be resulted by thinking of the grammatical correctness and the social functions of the sentence that we say should be done spontaneously.The results of this study would give the contribution to servers in order to improve the English speaking skills in serving food and beverage orders. Secondly, for the restaurant management in considering the policy of self-development of the servers to improve English speaking ability so that can consider the promotion policy for the servers who have speaking English skill well, and the last, the English lecturers at tourism colleges in developing approaches, methods and techniques of teaching English for communication and English for Specific Purpose (ESP).This study used a qualitative descriptive method to describe English speaking skill of 20 servers by evaluating language aspects in speaking such as the pronunciation, grammar, vocabulary, fluency, and comprehension in serving food and beverage orders of â€œAâ€™la carte menuâ€. Â Â Â Â Â Â Â Â Â Â Â Evidently, all the respondents do not have poor of English speaking skills.75% respondents has good category, 35% respondents has excellent category, and 10% has average category of English speaking skills. Based on the research, it was known that the characteristics of the sample can be fulfilled as required in the methodology of this study.